2020
DOI: 10.1002/jbm4.10392
|View full text |Cite
|
Sign up to set email alerts
|

Nonenzymatic and Trophic Activities of Carboxypeptidase E Regulate Bone Mass and Bioenergetics of Skeletal Stem Cells in Mice

Abstract: Bone and energy metabolism are integrated by common regulatory mechanisms. Carboxypeptidase E (CPE), also known as obesity susceptibility protein or neurotrophic factor‐α1, is recognized for its function in processing prohormones, including proinsulin and pro‐opiomelanocortin polypeptide. Independent of its enzymatic activity, CPE may also act as a secreted factor with divergent roles in neuroprotection and cancer growth; however, its role in the regulation of bone mass and skeletal cell differentiation is unk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
(53 reference statements)
0
7
0
Order By: Relevance
“…NF-α1/CPE applied extracellularly protected rat hippocampal primary neurons against H 2 O 2 -induced cytotoxicity by activating ERK and AKT signaling cascades, which increased pro-survival protein, BCL2 and decreased caspase-3 activation [ 14 , 15 ]. In murine skeletal stem cells, treatment with NF-α1/CPE activated ERK signaling and increased proliferation [ 16 ]. However, the mechanism of action of extracellular NF-α1/CPE in neuroprotection remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…NF-α1/CPE applied extracellularly protected rat hippocampal primary neurons against H 2 O 2 -induced cytotoxicity by activating ERK and AKT signaling cascades, which increased pro-survival protein, BCL2 and decreased caspase-3 activation [ 14 , 15 ]. In murine skeletal stem cells, treatment with NF-α1/CPE activated ERK signaling and increased proliferation [ 16 ]. However, the mechanism of action of extracellular NF-α1/CPE in neuroprotection remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Neurotrophic Factor-α1 (NF-α1), originally known as Carboxypeptidase E (CPE) was identified and shown to have a number of trophic effects [ 22 , 23 ], independent of its enzymatic activity; most notably in protecting neurons from stress-induced cell death in the hippocampal CA3 region in mice and was more critical than BDNF in this respect [ 24 ]. Studies using a mouse model expressing a non-enzymatic form of NF-α1/CPE demonstrated that it was as effective in neuroprotection as wild-type NF-α1/CPE [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…CPE is also associated with many metabolic disorders in the human body, including infertility, diabetes mellitus, obesity, glucose homeostasis, and bone remodelling. It also plays a crucial role in psychiatric and mental processes, including emotional responses, memory, and Alzheimer's disease [ 3 , [7] , [8] , [9] , [10] ].…”
Section: Introductionmentioning
confidence: 99%